Where The Trend Of Electric Motorcycle Growth Goes To ? A Study Of R-A Theory - abadi, yudha; Ihsan, Budi; Haris, Allan (Universitas Islam Negeri Raden Intan Lampung, 2025)
The trend of electric motorcycle sales growth, which promising, has not been in line with the level of consumer’s acceptance in Indonesia. Data shows that 54.9% stated they are not interested in buying electric motorcycles or cars. Objective: This study aims to understand the trend of increasing sales and the low adoption using R-A Theory. As a theory of competition’s process, this study aims to evaluate the main postulates of R-A Theory in the context of the electric motorcycle industry in Indonesia. The methodology used in this research is qualitative descriptive using literature review approach. The data collected from well-accredited sources involving previous papers, media exposure and government policy that available online. Findings: The results found that the promising growth triggered by Indonesian government’s policy still requires a comprehensive action needs to be done, indicating a real challenges in developing existing resources that affect the low acceptance of EV motorcycle and in turn its comparative advantage obstacles. One of this study’s novelties is the insight on R-A Theory development especially on building a collaborative ecosystem. This paper also contributes in describing the Comparative Advantage, Competitive Advantage and its challenges face by players in the electric motorcycle industries. Keywords : Competitive Advantage, Electric Motorcycle, Policy & Competition